PTH-041 Large (<4 cm) and giant (≥4 cm) colorectal polyps: comparison of piecemeal resection outcomes. (22nd June 2015) - Tsiamoulos, ZP; Elliott, T; Rameshshanker, R; Suzuki, N; Peake, S; Bourikas, L; Saunders, BP
Abstract : Introduction: Piecemeal Endoscopic Mucosal Resection (p-EMR) is a standard and safe endoscopic technique for resection of large colorectal polyps (>2 cm). Limited data are available regarding p-EMR of giant polyps (>4 cm). Method: A prospective study recording short and long-term outcomes after p-EMR for colorectal polyps > 2 cm between Jan 2010 and August 2012 was conducted. We compared two cohorts of patients: group-A with large polyps (2 to <4 cm) vs group-B with giant (≥4 cm) polyps. Chi-square/Fischer's tests were performed between categorical variables including patient demographics/polyp features/techniques applied {p-EMR with spiral snare and hybrid p-EMR). Our primary outcome was to compare the safety, efficacy and complication rate between the two groups. Results: Group-B patients were older than group-A patients (mean 70.6 vs. 67.8 yrs, p = 0.01) and were more likely to have come from a tertiary referral source (p = 0.05). Large polyp referrals were almost twice as frequent as giant polyp referrals (218 vs. 123, p < 0.001). Median polyp size was 2.5cm in group-A and 5cm in group-B. Giant polyps were most commonly found in the recto-sigmoid segment (26% rectum and 28% sigmoid, p < 0.001), whilst large polyps were more evenly distributed throughout the colon. No significant difference in cancer prevalence was recorded between the groups. Endoscopic excision was complete in 89% in large (median time 18min) and in 70% in giant groups (median time 38min). All large polyps were excised in one session, whilst 4% of giant polyps required more than one session. Incomplete submucosal lift (46% vs 63%, p = 0.002) and difficult polyp position (45% vs 63%, p < 0.001) were more common in giant polyps. Spiral snare EMR (6% vs 28%, p < 0.001) and hybrid (0% vs 7%, p < 0.001) techniques were more commonly used in giant than in large polyps. Procedural bleeding occurred more frequently in giant polyps (5% vs 17%, p < 0.001). Delayed bleeding was also significantly higher in giant polyps (15% vs 34%, p < 0.001), but hospitalisation or further intervention did not vary significantly by polyp size. The overall long-term recurrence at 24 months was 17% (11% vs 28%, p = 0.02). The follow up occurrence was more frequent for giant polyps at 3 month (43% vs 72%, p < 0.001) and 9 month (14% vs 26%, p = 0.007) intervals. Benign recurrence requiring surgery and the cancer prevalence did not vary between polyp size group. Conclusion: Piecemeal resection is a safe and efficacious modality for the resection of colorectal polyps >4 cm. However, these giant polyps more often require spiral snare or hybrid resection techniques and their higher adenoma recurrence rate post p-EMR may dictate shorter surveillance intervals. Disclosure of interest: None Declared.